Influence of Gas Physical Properties on Labyrinth Seals Throttling Characteristics - Bondarenko G.A.; Vanyeyev S.M.; Baga V.N.; Bashlak I.A.; Rodymchenko T.S. (Problems of the Regional Energetics)
The most important issue when designing the labyrinth sealing knots is the question of the cor-rectness of the model tests results application. This task has not had a strong solution so far. For practical calculations of labyrinth seals famous formulae for determining leakage through the hole are used. They are supplemented by coefficients obtained experimentally in conditions which practically had nothing to do with full scale ones: flat (non-circular) models are used, possible effect of the shaft rotation and the operating environment behavior are not taken into account. For the purpose of obtaining the answer to a question concerning the impact factor of gas physical properties on the flow characteristics of labyrinth seals a series of physical and nu-merical experiments on various gases were carried out. The studies were conducted under condi-tions maximum approximate to field ones. Pilot studies were conducted on a standard experi-mental bench to specify throttling characteristics of labyrinth seals. Numerical investigations were conducted using the СFD techniques on various gases. Numerical study and experiment confirmed the influence of gas physical properties on throttling characteristics of labyrinth seals. The heavier the gas the more intensive symptoms are. Flow coefficient divergence of the seal run by air and vapor is about 30%. It has been proved and confirmed by experiments. Visualiza-tion of flow has been obtained. Studies have shown a significant impact of gas physical proper-ties on leakage degree.